Pembelajaran Berdiferensiasi untuk Mengakomodasi Keberagaman Siswa di Sekolah Dasar - Juliana Margareta Sumilat; Koni Olive Tunas (Journal on Education, 2024)
The purpose of this research is to investigate how literature studies can be used to support student diversity in elementary schools. In elementary schools, student diversity encompasses differences in academic abilities, cultural backgrounds, languages, learning styles, and special needs. This research relies on the analysis of various literature covering differentiated learning theory, best practices in elementary schools, challenges, and benefits. Differentiated learning is an approach that modifies teaching methods to meet the unique needs of each student. The results of this literature review indicate that implementing differentiated learning can enhance student engagement, provide more attention to individual needs, and create an inclusive learning environment. This method can also help students with various skills develop according to their learning styles and paces.